QUBIC: The Q & U Bolometric Interferometer for Cosmology - Battistelli, E. S.; Ade, P.; Alberro, José Gabriel; Almela, Daniel Alejandro; Amico, G.; Arnaldi, L. H.; Auguste, D.; Bonaparte, J.; Bottani, A.; Di Donato, A.; Etchegoyen, Alberto; Fasciszewski, A.; et al. (Springer/Plenum Publishers, 2020)
Fil: Battistelli, E. S.. Universita di Roma La Sapienza; Italia